2008
DOI: 10.1051/0004-6361:20078815
|View full text |Cite
|
Sign up to set email alerts
|

Searching for cool core clusters at high redshift

Abstract: Aims. We investigate the detection of Cool Cores (CCs) in the distant galaxy cluster population with the purpose of measuring the CC fraction out to redshift 0.7 ≤ z < 1.4. Using a sample of nearby clusters spanning a wide range of morphologies, we define criteria to characterize cool cores, which are applicable to the high-redshift sample. Methods. We analyzed azimuthally-averaged surface brightness (SB) profiles with the known scaling relations, and we fitted single/double β models to the data. Additionally,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
320
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(354 citation statements)
references
References 57 publications
29
320
1
4
Order By: Relevance
“…This raises the possibility of identifying characteristic radii that are comparable across clusters via the surface brightness. To that end, we motivate a redshift-and temperaturedependent scaling of surface brightness based on the self-similar model of Kaiser (1986, see also Santos et al 2008).…”
Section: Standardizing Cluster Surface Brightnessmentioning
confidence: 99%
See 1 more Smart Citation
“…This raises the possibility of identifying characteristic radii that are comparable across clusters via the surface brightness. To that end, we motivate a redshift-and temperaturedependent scaling of surface brightness based on the self-similar model of Kaiser (1986, see also Santos et al 2008).…”
Section: Standardizing Cluster Surface Brightnessmentioning
confidence: 99%
“…Mohr et al 1993, Buote & Tsai 1995, Jeltema et al 2005, Nurgaliev et al 2013, Rasia et al 2013, and those which attempt to assess the presence or development of a cool core (e.g. Vikhlinin et al 2007, Santos et al 2008, Mantz 2009. 2 Automated algorithms based on such simple measurements are inevitably limited compared to visual classification, but their reproducibility, objectivity and particularly their straightforward applicability to data sets from large follow-up programs make them appealing.…”
Section: Introductionmentioning
confidence: 99%
“…8, the core region of the SB distribution at r < ∼ 100 kpc is now qualitatively better modelled. We also measured the surface brightness concentration for the cluster using the parameter c SB = (SB[r < 40 kpc)])/(SB[r < 400 kpc]) as defined by Santos et al (2008), which allows an improved structural characterization of high-z clusters compared to methods requiring very high photon statistics. For XMMU J1230.3+1339 this parameter is found to be c SB = 0.07, which places the system in the formal category of NonCool Core (NCC) clusters, in contrast to the more centrally concentrated objects in the moderate and strong Cool Core Cluster (CCC) class at high redshift (Santos et al 2008).…”
Section: Chandramentioning
confidence: 99%
“…Numerous studies have found evidence for ultraviolet (UV) and infrared (IR) continuum (e.g., McNamara & O'Connell 1989;Hicks & Mushotzky 2005;O'Dea et al 2008;McDonald et al 2011b;Hoffer et al 2012;Rawle et al 2012;Fraser-McKelvie et al 2014;Donahue et al 2015), warm, ionized gas (e.g., Hu et al 1985;Johnstone et al 1987;Heckman et al 1989;Crawford et al 1999;Edwards et al 2007;Hatch et al 2007;McDonald et al 2010McDonald et al , 2011a, and both warm and cold molecular gas (e.g., Jaffe & Bremer 1997;Donahue et al 2000;Edge 2001;Edge et al 2002;Edge & Frayer 2003;Salomé & Combes 2003;Hatch et al 2005;Jaffe et al 2005;Johnstone et al 2007;Oonk et al 2010;McDonald et al 2012c)-all of which are indicative of ongoing or recent star formation. Star-forming BCGs were found preferentially in galaxy clusters with "cool cores," as identified by a central density enhancement in the ICM (e.g., Vikhlinin et al 2007;Santos et al 2008;Hudson et al 2010) or low central entropy/cooling time (e.g., Cavagnolo et al 2008Cavagnolo et al , 2009Hudson et al 2010). These and other works established a link between the cooling ICM and the presence of multiphase gas, suggesting that cooling flows may indeed be fueling star formation in BCGs.…”
Section: Introductionmentioning
confidence: 99%